Associations of Serum High-Sensitivity C-Reactive Protein and Prealbumin with Coronary Vessels Stenosis determined by Coronary angiography and Heart Failure in Patients with Myocardial Infarction: hs-CRP and prealbumin PAB in myocardial infarction - Zhu, Yun; Yu, Zhen; Xu, Ronggui; Wang, Beibei; Lou, Yiqun; Zhang, Na; Chen, Ziyin (Journal of Medical Biochemistry, 2022)
Background: To explore the associations of serum high-sensitivity C-reactive protein (hs-CRP) and prealbumin (PAB) with the number of diseased coronary vessels, degree of stenosis and heart failure in patients with myocardial infarction (MI).Methods: A total of 39 MI patients treated in the Cardiology were selected as the observation group, and another 41 patients with normal results of coronary angiography during the same period were selected as the control group. The general data of patients were recorded in detail, the content of serum hs-CRP and PAB in the peripheral blood was detected, and the number of diseased coronary vessels and the degree of stenosis were detected via coronary angiography.Results: Compared with those in control group, the blood pressure and heart rate significantly rose, the content of indexes related to the severity of MI were significantly increased, the content of hs-CRP was significantly increased, and the content of PAB was significantly decreased in observation group. Hs-CRP was positively correlated with the number of diseased coronary vessels, degree of stenosis and heart failure in patients, but PAB was negatively correlated with the above factors. The survival rate of MI patients with high content of hs-CRP was obviously lower than that of patients with low content of hs-CRP.Conclusion: Serum hs-CRP and PAB are closely associated with the number of diseased coronary vessels, degree of stenosis and heart failure in MI patients.
Keywords: high-sensitivity C-reactive protein; prealbumin; myocardial infarction; coronary artery disease